2015
DOI: 10.1080/00015458.2015.11681061
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Parastomal Hernia Using Pre-peritoneal Mesh - Long Term Outcome of a Prospective Study

Abstract: Putting a pre-peritoneal polypropylene mesh is an easy, quick and inexpensive method, and easy to learn. The outcome is better than creating stomas without mesh, but further studies are needed to explore potential benefits of different types of mesh and their methods of positioning and anchoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Moreover, mesh application did not cause pain at the stomal site [25, 27]. Our pooled results are consistent with the findings of some non-RCTs that showed promising outcomes with mesh placement at the time of colostomy formation and absence of an increase in the complication rate [38, 47]. Lee et al performed a cost effectiveness analysis and found that the cost was lower and the ability to prevent parastomal hernia was greater with prophylactic mesh application in patients who underwent permanent colostomy than with the conventional method [48].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, mesh application did not cause pain at the stomal site [25, 27]. Our pooled results are consistent with the findings of some non-RCTs that showed promising outcomes with mesh placement at the time of colostomy formation and absence of an increase in the complication rate [38, 47]. Lee et al performed a cost effectiveness analysis and found that the cost was lower and the ability to prevent parastomal hernia was greater with prophylactic mesh application in patients who underwent permanent colostomy than with the conventional method [48].…”
Section: Discussionsupporting
confidence: 87%
“…Until now, the use of prosthetic mesh has not been widely accepted as a standard of preventive prosthetics in most surgical centers. I believe that the main reason is their lack of awareness of the almost inevitable development of parastomal hernia with long-term observation 56 . Prophylactic mesh placement has been shown to be effective in reducing the incidence of cPH and rPH based on randomized trials in patients undergoing colostomy surgery.…”
Section: Figure 4 Determining the Coordinates Of The Base Point Of The Ledmentioning
confidence: 99%